2019
DOI: 10.1111/ajco.13278
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of data feedback at lung cancer multidisciplinary team meetings: A mixed methods study

Abstract: Aim: Multidisciplinary team (MDT) meetings can facilitate optimal lung cancer care, yet details of structured data collection and feedback remain sparse. This study aimed to investigate data collection and the impact of feedback to lung cancer MDTs. Methods:A mixed-methods study using pre and post-test surveys, semistructured interviews, and observation to evaluate data collection and response to modeled data feedback in three Australian lung cancer MDTs at different locations and development stage (site A: ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Data feedback of recommendations is another important issue. Stone et al reported a mixed-methods study on the clinical impact of modeled data feedback at a lung cancer MTD based on pre-and post-surveys and semi-structured interviews at three Australian cancer centers [35]. Results demonstrated agreement if they reached C 4 values on a five-point Likert scale.…”
Section: Barrier and Facilitatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data feedback of recommendations is another important issue. Stone et al reported a mixed-methods study on the clinical impact of modeled data feedback at a lung cancer MTD based on pre-and post-surveys and semi-structured interviews at three Australian cancer centers [35]. Results demonstrated agreement if they reached C 4 values on a five-point Likert scale.…”
Section: Barrier and Facilitatorsmentioning
confidence: 99%
“…The quality of decisionmaking in MTD depends on the quality of records presented and team processes quality. Medical literature reports that MTD usually discusses 5-8 cases per meeting [35]. German investigators employed an adaptation of the observer rating scale Multidisciplinary Tumor Board Metric for the Observation of Decision-Making (MDT-MODe) to assess the quality of the presented information and team processes in 249 cases discussed at 29 MTBs [37].…”
Section: Quality Of Mtbmentioning
confidence: 99%
“…The proliferation of MDT-related research papers over recent years indicates a strong interest in MDT practice. Research from our group has identified positive responses from MDT clinicians to modelled data feedback, representing their own clinical cohorts (43).…”
Section: Discussionmentioning
confidence: 99%
“…National lung cancer audits such as in the UK above, Denmark (44) and the Netherlands (16,45) demonstrate the effects of systems that include institutional data feeds into national registries, portals for feedback and subsequent benchmarking. Smaller scale studies have tested details of audit and feedback to clinicians both in lung cancer (43,46) and other fields (47) but there is little if any (to our knowledge) literature on the effects of real-time, clinical data feedback to lung cancer MDTs on clinical outcomes. Cancer outcomes data are often delayed, even in this series of papers with an average of over four years between the data collection period and publication of the paper.…”
Section: Discussionmentioning
confidence: 99%
“…MDT performance must be quality assured both internally and by external review with demonstration of cost-effectiveness of quality improvements, and MDT guidance must be promoted nationally and written into national cancer plans. The use of tools and data feedback to improve MDT performance should be considered [174,175]. ‱ The ERQCC expert group strongly recommends that further attention be given to measures of patient reported outcomes, not only to agree which tools should be used, but also to use them more systematically as part of discussions and evaluation within the MDT.…”
Section: Mdt Performancementioning
confidence: 99%